Application of English as a Medium of Instruction Policy in a Private School in Nepal: An Examination - Giri, Prakash Chandra (Journal of NELTA, 2021)
English as a Medium of Instruction (EMI) has become an important academic issue for further discussion in the context of Nepalese education system. Many parents and community members believe it gives children a viable route toward Socio-economic mobility and global citizenship, although researchers have mixed opinions about its eﬀectiveness. In south Asian countries such as Nepal, EMI has been adopted as a mandatory practice as early as possible, particularly in the private schools and also increasingly in government schools. Based on a small-scale action research on teachers and students of a private school situated in the Western Nepal, this article examines the conditions in which the school level decision-makers are forced to adopt EMI as a school’s language-of-education policy. In this article, I analyze both students’ and teachers’ views and reflections on EMI to argue that it can be eﬀective and relevant if conducted in a way that suits the local context and enables participants to recognize its value.